Are Thyroid Autoimmune Diseases Associated with Cardiometabolic Risks in a Population with Normal Thyroid-Stimulating Hormone?. (10th October 2018) - Chen, Yi; Zhu, Chunfang; Chen, Yingchao; Wang, Ningjian; Li, Qin; Han, Bing; Zhao, Li; Chen, Chi; Zhai, Hualing; Zhang, Lijuan; Lu, Yingli
Abstract : Background . The interrelation between thyroid autoimmunity and cardiovascular risks is complex and has not been confirmed. This study aimed at evaluating whether there exists a relationship between thyroid autoimmune diseases (AITDs) and cardiometabolic risks in a large population with normal thyroid-stimulating hormone (TSH) levels. Methods . The data was obtained from a cross-sectional study (SPECT-China study). This study enrolled 9082 subjects (3948 males and 5134 females) above 18 years with normal TSH levels. AITD was defined according to the positivity of TPOAb and TgAb as well as thyroid ultrasonography (US) findings. Results . After full adjustment, TPOAb and/or TgAb positivity (TPO/TgAb (+)) was significantly associated with higher BMI, waist circumference (WC), and HbA1c only in women (P = 0.004, 0.026 and 0.032, respectively), while both TPO/TgAb positivity and US positivity (TPO/TgAb (+) and US (+)) were positively associated with BMI and WC in both genders (P = 0.002 and 0.020 in men;P < 0.001 and <0.001 in women). TPO/TgAb (+) and US (+) were positively associated with HOMA-IR in women (P = 0.021 ) as well. Binary logistic analysis showed that AITDs had increased risks of central obesity, hyperlipidemia, and metabolic syndrome only in women (allP < 0.05 ). Moreover, TPO/TgAb (+) and US (+) were associated with an increased risk of obesity for both genders (P = 0.014 in men andP = 0.006 in women). Conclusions . Thyroid autoimmunity was positively associated with HbA1c, HOMA-IR, obesity, central obesity, hyperlipidemia, and metabolic syndrome, especially in women. This highlighted that AITDs may be potential risk factors for cardiometabolic disorders even if one's TSH was within the reference range.